On corrosion of carbon steels in Callovo-Oxfordian clay: complementary EIS, gravimetric and structural study providing insights on long term behaviour in French geological disposal conditions. (September 2014) - Martin, F.; Perrin, S.; Fenart, M.; Schlegel, M.; Bataillon, C.
<x content-type="archive" xml:space="preserve">Abstract</x> Dedicated integrated experiments have been used to determine in situ the corrosion rate of carbon steels in geological repository mock-ups (90°C, anaerobic, slow synthetic water flux…). Electrochemical impedance spectroscopy (EIS) measurements were performed, allowing for the extraction of instantaneous corrosion rate. In a separate but comparable set-up, occasional sampling among a batch of fifteen equivalent cells was performed, allowing for both gravimetric measurements and corrosion products characterisation. In both cases, the corrosion rate decreases continuously but the stationary state seems not to be reached within the duration of the EIS experiment. The slow kinetics and pseudo steady state of the corrosion process are confirmed by post-exposure characterisation of the corrosion products by SEM, micro-Raman spectroscopy and micro-XRD, revealing the rapid formation of an iron phyllosilicate layer that may act as a barrier layer for diffusion of the species between the clay environment and the alloy. This analysis provides good confidence on long term (over a millennium) extrapolations made from the experimental data fits, leading to an estimation of reasonable cumulated damages in the [40;120] μm range after 1000 years exposure.